Relationship between physical, anatomical and strength properties of 3-year-old cultivated tropical bamboo gigantochloa scortechinii - Razak Wahab; Mohd Tamizi Mustafa; Shafiqur Rahman; Mohamed Abdus Salam; Othman Sulaiman; Mahmud Sudin; Mohd Sukhairi Mat Rasat (ARPN, 2012)
The physical, anatomical and strength properties of 3-year-old cultivated tropical bamboo Gigantochloa scortechinii was studied. Five (5) culms of the bamboo were selected and harvested from the Bambusetum plot located in the Forest Research Institute Malaysia in Kepong. The anatomical study focussed on the vascular bundles and fibres located at the internodes and nodes No. 8 at the outer, middle and inner cross section of the bamboo. The sizes of the vascular bundles length, vascular bundles width, fiber length, fiber diameter, fiber lumens diameter, fiber walls thickness and fiber Runkle’s ratio were measured in relation to the samples positions at the internodes, nodes, and positions in the cross-section of the bamboo culms. The physical study gives emphasis on the moisture content, basic density and dimensional stability. The strength properties study focused on the tension parallel to the grain and shear test. Both the physical and strength study were conducted at internodes and nodes No. 8 of the bamboo.